The effect of targeted resistance training on bench press performance and the alternation of prime mover muscle activation patterns. Issue 10 (26th November 2022) - Stronska, Katarzyna; Golas, Artur; Wilk, Michal; Zajac, Adam; Maszczyk, Adam; Stastny, Petr
ABSTRACT: Targeted muscle strengthening might improve performance or help overcome training stagnation; therefore, the aim of the present study was to investigate changes in muscle activity patterns before and after six weeks of targeted resistance training. Twenty-seven resistance-trained men were divided into three groups according to their prime mover activity, as measured by surface electromyography during a bench press (BP). Each group underwent a six-week block of targeted exercises for one of the following muscles: anterior deltoid (AD), pectoralis major (PM) or triceps brachii (TB). ANOVA showed that each group increased their 1 repetition maximum (1RM) (p < 0.05) and the activity of the exercised muscle group during an isometric bench press (p < 0.01) and during a dynamic bench press (p < 0.01) at 85% of the 1RM. During the isometric BP, the TB training group had an increase in TB activity in comparison to the other groups. Targeted muscle training is a useful method for muscle activity increase and increasing the maximum strength in complex exercise, when applied in activity-deficient muscle groups. Strengthening the TB elicits changes in all prime movers and results in TB activity domination during a bench press.